Fire weather : a true story from a hotter world - Vaillant, John (Alfred A. Knopf, 2023)
"In May 2016, the city of Fort McMurray in Alberta, Canada, burned to the ground, forcing 88,000 people to flee their homes. It was the largest evacuation ever of a city in the face of a forest fire, raising the curtain on a new age of increasingly destructive wildfires. This book is a suspenseful account of one of North America's most devastating forest fires-and a stark exploration of our dawning era of climate catastrophes"--